Direct Nitrate Reductase Assay for detection of drug resistance in Mycobacterium tuberculosis: rapid, simple and inexpensive method for low resource laboratories - Lamsal, A; Thapa, B; Timilshina, M; Verma, SC; Ghimire, GR; Gautam, A (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: The most common method for detection of drug-resistant-Tuberculosis (DR-TB) in resource-limited settings (RLSs) is indirect susceptibility testing on Lowenstein-Jensen (LJ) medium with results available only after 2-3 months. Rapid detection of drug resistance by direct Nitatre Reductase Assay (NRA) expedites Tuberculosis patient management. The objective of the study is to access the feasibility and performance of Direct NRA for detection of DR-TB in National Tuberculosis Center under the National Tuberculosis Control Programme (NTP). MATERIALS AND METHODS: Out of 416 previously treated and new pulmonary TB suspect cases; a total of 117 (28.1%) smear-positive sputa with a positivity score of 1+ or more were used in the study. The NRA results were compared with the gold standard LJ proportion method for 110 (94%) specimens while 7 were either contaminated or culture negative. RESULTS: In comparison with LJ proportion method, the respective sensitivities, specificities, NPV, PPV and kappa agreement were 97.2% (95% CI, 86-100), 95.9%(95% CI, 89-99), 92.1% (95% CI, 78-99) 98.6% (95% CI, 92-100), and 0.92 for INH, 100% (95%CI, 90-100), 98.7% (95% CI, 93- 100), 97.1% (95% CI, 85-100), 100% (95% CI, 95- 100) and 0.98 for RFM, 97.1% (95% CI, 85-100) ,96.1% (95%, 89-99), 91.7% (95% CI, 78-98), 98.7% ((95% CI, 93-100) and 0.92 for SM and 100% (95% CI, 88-100), 97.7% (95% CI, 91-100), 93.3% (95% CI, 78-99), 100% (95% CI, 95- 100)and 0.93 for EMB. CONCLUSIONS: The results obtained by direct NRA demonstrated excellent concordance for all drugs. Direct NRA is an assay which detects DR-TB directly from sputum rapidly and has the potential to become an alternative to existing methods particularly in resource-poor settings. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8319 Int J Infect Microbiol 2013;2(2):34-39